Willingness, refusal and influential factors of parents to vaccinate their children against the COVID-19: A systematic review and meta-analysis - Galanis, Petros; Vraka, Irene; Siskou, Olga; Konstantakopoulou, Olympia; Katsiroumpa, Aglaia; Kaitelidou, Daphne (Preventive medicine, 2022)
We aimed to estimate parents' willingness and refusal to vaccinate their children against the COVID-19, and to investigate the predictors for their decision. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. We searched Scopus, Web of Science, Medline, PubMed, CINAHL and medrxiv from inception to December 12, 2021. We applied a random effect model to estimate pooled effects since the heterogeneity was very high. We used subgroup analysis and metaregression analysis to explore sources of heterogeneity. We found 44 studies including 317,055 parents. The overall proportion of parents that intend to vaccinate their children against the COVID-19 was 60.1%, while the proportion of parents that refuse to vaccinate their children was 22.9% and the proportion of unsure parents was 25.8%. The main predictors of parents' intention to vaccinate their children were fathers, older age of parents, higher income, higher levels of perceived threat from the COVID-19, and positive attitudes towards vaccination (e.g. children's complete vaccination history, history of children's and parents' vaccination against influenza, confidence in vaccines and COVID-19 vaccines, and COVID-19 vaccine uptake among parents). Parents' willingness to vaccinate their children against the COVID-19 is moderate and several factors affect this decision. Understanding parental COVID-19 vaccine hesitancy does help policy makers to change the stereotypes and establish broad community COVID-19 vaccination. Identification of the factors that affect parents' willingness to vaccinate their children against COVID-19 will provide opportunities to enhance parents' trust in the COVID-19 vaccines and optimize children's uptake of a COVID-19 vaccine. •Parents' willingness to vaccinate their children against the COVID-19 is moderate.•Parents' willingness ranges from 25.6% to 92.2%.•Several factors affect parents' decision, e.g. fathers, older age of parents, etc.•Policy makers should understand parental decision around COVID-19 vaccination.